Developing effective warm-ups - Durand, B. (2009)
This workshop presented by Short Track strength and conditioning coach, Bruno Durand, will examine the importance of implementing effective warm-ups in the club environment from an early age both as a means of injury prevention and to reinforce the development of the ABCs. This workshop will walk coaches through the fundamental principles of how to develop an effective warm-up and implement it in the club environment.